1972
DOI: 10.1037/h0033610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a visual frame and vertical-horizontal illusion on shape and size perception.

Abstract: A variety of visual frames and of stimulus shapes are examined in a series of three experiments to investigate.the magnitude of the frame's effect on apparent size and apparent shape. Although a slight frame effect is demonstrated under very special conditions, its importance to the perceptual experience is questioned. The predominating effect of the vertical-horizontal phenomena is also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
3
5
1
Order By: Relevance
“…He found that the overestimation of the vertical line was enhanced when surrounded by a horizontally oriented frame, and that it was reduced-but not eliminated-by a vertically oriented frame. These results were replicated by Houck, Mefferd, and Greenstein (1972). However, none of these studies explicitly compared monocular and binocular viewing of differently oriented visual fields.…”
Section: This Effect Significantly Interacted With Lighting Conditionsupporting
confidence: 77%
“…He found that the overestimation of the vertical line was enhanced when surrounded by a horizontally oriented frame, and that it was reduced-but not eliminated-by a vertically oriented frame. These results were replicated by Houck, Mefferd, and Greenstein (1972). However, none of these studies explicitly compared monocular and binocular viewing of differently oriented visual fields.…”
Section: This Effect Significantly Interacted With Lighting Conditionsupporting
confidence: 77%
“…In this second experiment, we used the same configurations and line extension task than in the first experiment but changed the rectangular artificial background frames by curvilinear frames. This time the expected frame effect is significant, which confirms results obtained in previous studies (Houck, Mefferd, & Greenstein, 1972;Ku¨nnapas, 1957bKu¨nnapas, , 1959 Figure 5. Degree of illusion and participants' dispersion in each visual frame when extending vertical or horizontal lines (collapsed configurations) in Experiment 2.…”
Section: Methodssupporting
confidence: 91%
“…Sleight and Austin (1952) could not in general replicate Fick's observations except for circles and ellipses. In turn, Houck, Mefferd, and Greenstein (1972) could not replicate Sleight and Austin but found some support for Fick's observations on rectangles and squares. Fick's (1851) explanation of the illusion in terms of astigmatism also instigated…”
contrasting
confidence: 66%